Age at Diagnosis Is Determinant for the Outcome of Inflammatory Bowel Disease: Is It a Myth?. Issue 2 (15th February 2021) - Ministro, Paula; Dias, Cláudia Camila; Portela, Francisco; Fernandes, Samuel; Bernardo, Sónia; Pires, Francisco; Lago, Paula; Rosa, Isadora; Trindade, Eunice; Alves, Catarina; Correia, Luís; Magro, Fernando
Abstract : INTRODUCTION: Patients with elderly-onset inflammatory bowel disease were previously associated with a less aggressive course of the disease. However, there are conflicting data that need further validation. We aimed to determine the association between age at diagnosis and the development of progressive disease in patients with Crohn's disease (CD) and ulcerative colitis (UC). METHODS: This cohort study included patients with CD and UC followed in 6 secondary and tertiary care centers in mainland Portugal. Patients were divided into a derivation (80%) cohort and a validation (20%) cohort. The primary outcome was progressive disease. Logistic regression analysis, receiver operating characteristic curves, and the areas under the curve (AUC) were performed. Odds ratios with 95% confidence intervals (CIs) were estimated. RESULTS: The derivation cohorts included 1245 patients with CD (68% with progressive disease) and 1210 patients with UC (37% with progressive disease), whereas the validation cohorts included 302 patients with CD and 271 patients with UC, respectively, with similar outcome proportions. In our final model, age at diagnosis older than 60 years was significantly associated with a lower risk of developing progressive disease (odds ratio 0.390, 95% CI 0.164–0.923, P = 0.032), with a high discriminative power (AUC 0.724, 95% CI 0.693–754) in patients with CD. However, according to this model, no significant associations were found between age at diagnosis and the risk of developing progressive disease in patients with UC. No differences were observed in the AUC values between the validation and the derivation cohorts. DISCUSSION: Patients with elderly-onset CD, but not patients with UC, were associated with a less progressive course of the disease.